To Have A Self Or To Be A Non-Self: ‘Having’ And ‘Being’ Modes In Relation To Existential And Buddhist Understanding (Existential Analysis: Journal of the Society for Existential Analysis, 2018)
In To Have or To Be? Erich Fromm discussed 'having' and 'being' modes, the former linked to 'things' and consumerism, the latter to 'process' and spiritual life. This article explores Fromm's ideas of having and being modes in relation to existential and Buddhist understandings of self/non-self and considers some implications.
Keywords: Having; being; existential; Buddhism; self-construct; non-self; ontological security